PENGARUH PENGALAMAN KOGNITIF DAN PENGALAMAN AFEKTIF TERHADAP NILAI YANG DIRASAKAN DAN NIAT BELI PADA APLIKASI DULUX VISUALIZER - Syarifah Hudayah; Herning Indriastuti; Nur Ita’ Zahrah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the effect of Cognitive Experience and AffectiveExperience on Perceived Value and Purchase Intention in the Dulux Visualizerapplication. Sometimes the use of AR technology does not match consumerexpectations, such as imitation products on AR technology that do not match whatconsumers imagine in the real world. This phenomenon can reduce the purchaseintention of consumers in buying a product. The sample in this study wererespondents who had used the Dulux Visualizer application as many as 190 users Data collection method is done by distributing questionnaires. This study uses adata analysis tool using the Analysis of Moment Structure (AMOS) analysismethod. The results showed that 1) Cognitive experience had a positive andinsignificant effect on perceived value, 2) Affective experience had a positive andsignificant effect on perceived value, 3) Cognitive experience had a positive andsignificant effect on purchase intention, 4) Affective experience had a positive andsignificant effect on perceived value. significant effect on purchase intention, 5)perceived value has a positive and significant effect on purchase intention, 6)cognitive experience has positive and insignificant effect on purchase intentionthrough perceived value, and 7) affective experience has positive and insignificanteffect on purchase intention through value that is felt.